Influence of gestational exercise practice and litter size reduction on maternal care. (10th January 2021) - August, Pauline Maciel; Rodrigues, Karoline dos Santos; Klein, Caroline Peres; dos Santos, Bernardo Gindri; Matté, Cristiane
Highlights: Maternal swimming exercise did not alter maternal behavior. Litter reduction increased the lactation frequency in the first postnatal days. Litter reduction decreased dams' total time out of the nest. Maternal exercise decreased the lactation frequency induced by litter size reduction. Abstract: Mother-pup interactions are extremely important to offspring survival and growth. The goal of this study was to evaluate the influence of prenatal and neonatal interventions on maternal care, analyzing the effect of maternal exercise, as a healthy intervention, and also the litter size reduction, a model that has been widely used to study early overfeeding in rats. Female Wistar rats were divided into 1) sedentary, and 2) swimming exercise for four weeks, starting one week before mating (5 days/week, 30 min/session). One day after birth, the litter was culled to 8 pups (normal) or 3 pups (small) per dam, yielding control and overfed subgroups for each maternal group, respectively. From postnatal days 2–9 the litter was observed 5 periods a day, to evaluate maternal behavior. Litter reduction caused important alterations in maternal behavior, reducing the total time out of the nest and increasing the frequency of maternal care and lactation in several observation periods, justifying the increased pup's weight gain already demonstrated by this animal model. The practice of maternal exercise did not prevent, but cause the less intensive frequency of non-maternal behavior and lactation in arched-back position, induced by the reduction of litter size. These data demonstrated that small litter size altered maternal behavior, and gestational exercise does not influence significantly these changes.